2019
DOI: 10.1101/691170
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interictal discharges spread along local recurrent networks between tubers and surrounding cortex

Abstract: The presence of interictal epileptiform discharges on electroencephalography (EEG) may indicate increased epileptic seizure risk and on invasive EEG are the signature of the irritative zone. In highly epileptogenic lesions -such as cortical tubers in tuberous sclerosis -these discharges can be recorded with intracranial stereotactic EEG as part of the evaluation for epilepsy surgery. Yet the network mechanisms that underwrite the generation and spread of these discharges remain poorly understood, limiting thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…This concept of the tuber core driving the dynamics has also been shown in a dynamic causal modelling study, which showed that ictal and interictal dynamics were best supported by a model where an impulse was triggered at the tuber core. 25 This is supported by another single patient single unit study which showed a gradient of epileptogenicity within tubers, with more neurons being modulated by interictal epileptiform discharges in the tuber compared to the periphery. 26 Together, these works support a complex interaction within and between tubers that needs to be considered before deciding on treatment strategies including surgical resection of potentially epileptogenic tubers.…”
Section: Discussionmentioning
confidence: 75%
“…This concept of the tuber core driving the dynamics has also been shown in a dynamic causal modelling study, which showed that ictal and interictal dynamics were best supported by a model where an impulse was triggered at the tuber core. 25 This is supported by another single patient single unit study which showed a gradient of epileptogenicity within tubers, with more neurons being modulated by interictal epileptiform discharges in the tuber compared to the periphery. 26 Together, these works support a complex interaction within and between tubers that needs to be considered before deciding on treatment strategies including surgical resection of potentially epileptogenic tubers.…”
Section: Discussionmentioning
confidence: 75%
“…Resting state EEG can be used to construct a computational biomarker of idiopathic generalized epilepsy for the diagnostic process, which can be inferred from the extent of synchrony between EEG channels and the normalized power spectrum of the clinical data [102]. Recent work using network control theory and dynamic causal modelling provides a new perspective of analysing data and simulating epileptic brains as a whole network [103,104].…”
Section: Surgical Interventionmentioning
confidence: 99%
“…Observing seizures at this new scale has led to the idea that the cortical areas involved can be divided into a core territory of recruited neurons (the 'ictal core'), surrounded by areas that receive intense synaptic input but do not show hypersynchrony and pathologically high firing rates (the 'ictal penumbra'). Observations at the microscale have also revealed previously unobserved temporal phenomena at play during epileptic seizures: individual ictal and interictal epileptiform discharges observed on intracranial EEG (iEEG) can spread near-synchronously across macroscopic brain areas 8,9 . In contrast, microscale neurophysiological markers of the so-called 'ictal wavefront' spread locally at much slower speeds, typically not exceeding ~5 mm/s 10 .…”
Section: Introductionmentioning
confidence: 95%